Cancer Therapy: Synergized Multimodal Therapy for Safe and Effective Reversal of Cancer Multidrug Resistance Based on Low‐Level Photothermal and Photodynamic Effects (Small 31/2018). Issue 31 (2nd August 2018) - Xu, Luming; Liu, Jia; Xi, Jiangbo; Li, Qilin; Chang, Bingcheng; Duan, Xianming; Wang, Guobin; Wang, Shuai; Wang, Zheng; Wang, Lin
Abstract : In article number1800785, Guobin Wang, Shuai Wang, Zheng Wang, Lin Wang, and co‐workers fabricate a versatile nanoplatform composed of gold‐nanodot‐decorated hollow carbon nanospheres with hyaluronic acid coating (AuHCNs‐HA). Such a nanoplatform serves as a trimodal drug delivery and therapeutic system. Using this system, their work reveals that weak photothermal effects and weak photodynamic effects are quantitatively and functionally sufficient to augment chemotherapy efficacy towards effectively reversing cancer multi‐drug resistance with excellent biosafety.